Functional variant rs12614 in CFB confers a low risk of IgA nephropathy by attenuating complement alternative pathway activation in Han Chinese - Shi, Dian-Chun; Feng, Shao-Zhen; Zhong, Zhong; Cai, Lu; Wang, Meng; Fu, Dong-Ying; Yu, Xue-Qing; Li, Ming (Frontiers in Immunology, 2022)
Activation of the alternative pathway (AP) of complement is thought to play an important role in IgA nephropathy (IgAN). Our previous study showed that rs4151657 within the complement factor B (CFB) gene increased the risk of IgAN. The protein encoded by the CFB gene is an initial factor that promotes AP activation. The aim of this study was to investigate whether other variants of CFB conferred susceptibility to IgAN and elucidated their potential roles in AP activation. A total of 1350 IgAN patients and 1420 healthy controls were enrolled and five tag-single-nucleotide polymorphisms were selected for genotyping. The levels of key AP components, such as CFB, complement factor H and complement split product C3a, were measured by enzyme-linked immunosorbent assay. Molecular docking and molecular dynamic simulation were carried out to characterize the mutation of residues in the protein structure and the dynamic properties of wide type and mutation models of CFB protein. The allele-specific effect on CFB expression and its binding affinity to C3b were investigated through cell transfection and surface plasmon resonance analysis, respectively.We found that rs12614 significantly reduced the risk of IgAN (OR = 0.69, 95% CI = 0.52-0.91, P = 0.009), and the rs12614-T (R32W mutation) was correlated with lower CFB levels, higher serum C3 level and less mesangial C3 deposition in IgAN patients. The structural model showed that the R32W mutation reduced the structural stability of CFB protein. Furthermore, in vitro study revealed that rs12614-T decreased the expression of CFB and reduced its binding affinity to C3b by 4-fold compared to rs12614-C. In conclusion, the rs12614-T in CFB was associated with low risk of IgAN probably by attenuating AP activation.